Effects of cocaine under concurrent fixed ratio schedules of food and IV drug availability: a novel choice procedure in monkeys - Paronis, Carol A.; Gasior, Maciej; Bergman, Jack (Psychopharmacologia, 2002)
The relative reinforcing strength of cocaine can be characterized by the distribution of operant behavior during the availability of other reinforcing stimuli. To develop a procedure to rapidly evaluate the relative reinforcing strength of cocaine in monkeys. Monkeys were trained to respond on two levers under concurrent fixed-ratio 30 (FR30) schedules of reinforcement. Responding on one lever resulted in food delivery, responding on the alternative lever resulted in delivery of IV saline or cocaine (0.032 or 0.1 mg/kg per injection). Daily sessions consisted of three 30-min components separated by 10-min timeout periods. The availability of saline, 0.032, or 0.1 mg/kg per injection cocaine varied across components, and only in an ascending order. The relative reinforcing strength of 0.0032-0.32 mg/kg per injection cocaine was examined by substituting different unit doses for the training doses of cocaine. Effects of cocaine pretreatment on response distribution were determined by giving IM injections of 0.1-1.8 mg/kg cocaine 10 min prior to sessions of saline availability. Increasing unit doses of cocaine monotonically increased the distribution of responding on the injection-lever and monotonically deceased response rates. Responding occurred predominantly on the food-lever during availability of saline or 0.0032 mg/kg per injection cocaine, whereas availability of 0.032-0.32 mg/kg per injection produced >90% of responding on the injection-lever. Availability of 0.01 mg/kg per injection cocaine resulted in approximately equal levels of responding on the food- and injection-levers. Presession IM cocaine injections dose-dependently increased responding on the injection-lever. Stable behavior can be maintained under concurrent FR schedules of food and cocaine presentation in monkeys, and the distribution of behavior on food- and injection-levers is dependent on the available dose of cocaine.